“An Analysis of Emotional Meaning in John Lennon’s “Imagine” through Halliday’s Systemic Functional Linguistics” - Musthafa Kemal Pasha; Yusmar Amalia Soleha; Sabriena Dhea Azzahra; Mayang Sandyo Anggoro (Publikasi Inspirasi Indonesia, 2026)
This study used the Systemic Functional Linguistics (SFL) approach to analyze the emotional value of John Lennon's song